Understanding the Global TV Format - Moran, Albert; Malbon, Justin (Intellect Books, 2006)
This volume presents a series of papers concerned with the interrelations between the postmodern and the present state of art and design education. Spanning a range of thematic concerns, the book reflects upon existing practice and articulates revolutionary prospects potentially viable through a shift in educative thinking.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Asia: New Growth Areas - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
The previous chapter introduced in broad brushstrokes the issues at stake in this study, beginning with a critique of globalization and moving on to sketch in ﬁner detail national television systems, the role of local content, and the economic importance of formats. The chapter concluded with a brief overview of the vagaries of copyright law as it applies to formats. Here, we initiate a discussion of Asian television systems beginning with a much different perspective on the ramiﬁcations of cultural borrowing. In this context we note that the format business straddles the divide between creative endeavour and innovation on the one hand, and slavish imitation on the other. This polarization manifests in widespread misunderstanding of the goals of format producers and distributors, and the role that formats play in the shaping of television schedules. We need therefore to ﬂesh out the in-between issues. These are primarily concerned with the relationship between the format and its localization, television consumption within ‘cultural continents’, and changes in media systems. Taking this further we note the relationship between production and reception within Asia, the growth of television industries in the region and the relationship between formatting and new media distribution platforms that use interactive technologies allowing viewers to feedback responses. This exercise enables us to identify an alternative list of conceptual tools to those championed by political economy scholars.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Feeling Glocal: Japan in the Global Television Format Business - Iwabuchi, Koichi (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In March 2001 a Japanese newspaper report entitled ‘Indians are addicted to a quiz show’ drew attention to a phenomenally popular television programme in India – a quiz show that attracts millions of viewers in which challengers strive to win prize money (Asahi Shinbun 2001). What was particularly eye-catching for the journalist was the proﬂigately decorated studio set located in Mumbai (Bombay) and the caring guidance of the MC, a ﬁlm star famous in India. The name of the show, as you might have already inferred, was Who Wants To Be A Millionaire?.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Japon (corpus analysé); Japon (lieu de production du savoir); _Nettoyé

A Local Mode of Programme Adaptation: South Korea in the Global Television Format Business - Lee, Dong-Hoo (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television has been called ‘a Western-originated project’ (Barker 1997: 5) and an institution of Western capitalist modernity. The global circulation of Western-centred, or more speciﬁcally, American-centred cultural products, contributes to the formation and dissemination of a global shared culture that reaches across the boundaries of nation-states. In the process American cultural products play a role in the formation of local television cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Corée du Sud (corpus analysé); Corée du Sud (lieu de production du savoir); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé